104 Analysis of clinical characteristics, genetic basis, management and arrhythmic outcomes of patients with catecholaminergic polymorphic ventricular tachycardia from a chinese city. (6th June 2022) - Tse, Gary; Lee, Sharen; Bin Waleed, Kahlid; Hui, Jeremy Man Ho; Lakhani, Ishan
Abstract : Introduction: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare cardiac ion channelopathy. The aim of this study is to examine the clinical characteristics, genetic basis and arrhythmic outcomes in CPVT patients from the Hong Kong city of China. Methods: This analysis was based on a wider study on ventricular arrhythmias that received approval from the local research ethics committee. Patients diagnosed with CPVT at public hospitals or clinics were included. The primary outcome was spontaneous ventricular tachycardia/ventricular fibrillation (VT/VF). Results: A total of 16 (mean presentation age=11±4 years old) patients were included. All patients presented at or before 19 years of age. Fifteen patients (93.8%) were initially symptomatic. Ten patients had both premature ventricular complexes (PVCs) and VT/VF, whereas one patient had PVCs without VT/VF. Genetic tests were performed in 14 patients (87.5%). Eight (57.1%) tested positive for the RyR2 gene. Seven variants have been described else-where (c.14848G>A, c.12475C>A, c.7420A>G, c.11836G>A, c.14159T>C, c.10046C>T and c.7202G>A). c.14861C>G is a novel RyR2 variant that has not been reported outside this cohort. All patients were treated with beta-blockers, three patients received amiodarone and two received verapamil. Sympathectomy (n=8) and implantable-cardioverter defibrillator implantation (n=3) were performed. Over a median follow-up of 127 (IQR: 97–143) months, six patients suffered from incident VT/VF. No significant predictors were identified on Cox regression. Conclusion: All CPVT patients from Hong Kong presented at or before 19 years of age. Genetic variants in RyR2 were identified. Declaration: A Preprint of this study has been published on Medrxiv. Conflict of Interest: None